Processing and electromechanical properties of lead zirconate titanate thick films by electrophoretic deposition. (12th May 2015) - Abellard, A.-P.; Kuscer, D.; Lethiecq, M.; Malic, B.; Levassort, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Electrophoretic deposition (EPD) was used for the fabrication of piezoelectric [lead zirconate titanate (PZT)] thick films on alumina substrates. The EPD was performed in constant current mode from an ethanol based suspension consisting of PZT and PbO particles. The influence of addition of ethyl cellulose (EC) and sintering temperature on the thickness, density, homogeneity and functional response of PZT thick films is studied. Results show that the highest electromechanical performance is obtained for the PZT thick films sintered at 900 or 950°C, with a thickness coupling factor kt of 50%. The addition of EC influenced the thickness of the PZT thick films but had only minor effect on the porosity content for sintering temperatures over 900°C. Moreover, elastic constants of the thick films based on the suspension with EC were lower, which leads to lower acoustic impedance (15 MRa) while maintaining high (kt) value. In this last case, a better acoustic matching can be expected with propagation media such as water or biological tissues for ultrasound medical imaging applications.